Assessment of muscle damage using magnetic resonance imaging data in dermatomyositis and sporadic inclusion body myositis - A. A. Kolomeychuk; L. P. Ananyeva; L. V. Ptichkina; A. N. Khelkovskaya-Sergeeva; D. O. Kazakov (Современная ревматология, 2025)
Idiopathic inflammatory myopathies (IIM) are a group of rare autoimmune diseases characterized by muscle weakness. IIMs are characterized by heterogeneity of manifestations and include several variants, each of which has peculiarities related to pathogenesis and autoantibody profile, clinical presentation, prognosis and response to therapy. In this context, the importance of early diagnosis and correct interpretation of clinical, laboratory and instrumental data is becoming increasingly important in order to recognize the phenotype of IIM in time.An important tool for the assessment of muscle damage is magnetic resonance imaging (MRI), which provides detailed anatomical and topographical information about muscles and adjacent soft tissues. The characteristics of the MRI of the muscles in different IIM phenotypes have not been sufficiently investigated.Objective: to evaluate and compare magnetic resonance (MR) signs of muscle damage in patients with dermatomyositis (DM) and sporadic inclusion body myositis (SIBM).Material and methods. The prospective study included 30 patients with IIM, including 15 with DM and 15 with SIBM. The diagnosis was based on the 2017 EULAR/ACR classification criteria. MRI of the thigh and calf muscles was performed using a Philips Multiva 1.5 TESLA (Philips, the Netherlands), and the intensity of muscle tissue edema and fatty replacement were assessed using a 4-point scale, as well as the total score and aggregated score by muscle groups according to the topographic and anatomical structure.Results and discussion. The total edema score was statistically significantly higher in DM than in SIBM (p<0.001). In contrast, the total fatty replacement score and the aggregated score of all thigh muscle groups (anterior, p><0.001; posterior, p=0.03; medial, p=0.02) were significantly higher in SIBM than in DM. In contrast to DM, all patients with SIBM had two additional MR signs: "distal gradient" and the "undulating fascia" symptom. No statistically significant differences were found between the compared IIM variants in the assessment of the total and aggregated edema score of calf muscle. At the same time, when assessing fatty replacement, the total and aggregated score in the anterior, posterior and lateral muscle groups were significantly higher in SIBM than in DM. Thus, the leading MR sign in DM was edema mainly in the anteromedial and posterior muscle groups of the thighs (due to the semitendinosus and semimembranosus muscles) and the anteroposterior calf muscle group. In SIBM, fatty replacement predominates in the anterior muscle group of the thighs and in the anterolateral and posterior calf muscle groups. Conclusion. The MR features of two clinically distinct variants of IIM, DM and SIBM are demonstrated, which reflect the heterogeneity of this disease group. MRI may be an informative method to identify MR patterns within the IIM group. Keywords: magnetic resonance imaging; diagnostics; inflammatory myopathies> < 0.001). In contrast, the total fatty replacement score and the aggregated score of all thigh muscle groups (anterior, p < 0.001; posterior, p=0.03; medial, p=0.02) were significantly higher in SIBM than in DM. In contrast to DM, all patients with SIBM had two additional MR signs: "distal gradient" and the "undulating fascia" symptom. No statistically significant differences were found between the compared IIM variants in the assessment of the total and aggregated edema score of calf muscle. At the same time, when assessing fatty replacement, the total and aggregated score in the anterior, posterior and lateral muscle groups were significantly higher in SIBM than in DM. Thus, the leading MR sign in DM was edema mainly in the anteromedial and posterior muscle groups of the thighs (due to the semitendinosus and semimembranosus muscles) and the anteroposterior calf muscle group. In SIBM, fatty replacement predominates in the anterior muscle group of the thighs and in the anterolateral and posterior calf muscle groups.Conclusion. The MR features of two clinically distinct variants of IIM, DM and SIBM are demonstrated, which reflect the heterogeneity of this disease group. MRI may be an informative method to identify MR patterns within the IIM group.